LITERATURA INFANTIL E BIBLIOTECA ESCOLAR COMO ESTRATÉGIA METODOLÓGICA PARA O DESENVOLVIMENTO DA LEITURA NA ESCOLA MUNICIPAL DE EDUCAÇÃO INFANTIL ODILÉIA DA SILVA BRITO, NO MUNICÍPIO DE PORTEL – MARAJÓ – PARÁ - LIMA, José Maria Soares de (2024)
During childhood, children are more likely to develop habits that may be present throughout their lives. Therefore, we consider it of fundamental importance that we encourage children to acquire a taste for reading. Children's literature, in this sense, provides a reorganization of world perceptions and development of the child's critical sense. The present study aims to investigate the reality of children from a municipal public school regarding their involvement with Children's Literature. We necessarily conducted a literature search and a field study, with a qualitative approach, conducted in a public school in the municipality of Portel, through a semi-structured interview with students of elementary school year of shift. Data analysis configured a low annual reading frequency by students, little interest of parents in the purchase of books for their children and restricted use of the library as a reading space. On the other hand, it was observed through this analysis that most students remember the books read and report that they like reading more than listening to stories, which highlights their ability to interpret reading. Thus, it is necessary to take measures to stimulate students' reading habits, such as rethinking the school library, making it dynamic, with active participation of students, and promoting a joint action of the school / student / family triad, of fundamental importance for the pedagogical process and the reader's formation.